PACKAGE FLUIDS 1. COMPUTER PROGRAMS FOR ANALYSIS OF FLUID INCLUSION DATA AND FOR MODELLING BULK FLUID PROPERTIES - Bakker R.L. (My University, 2003)
The computer package FLUIDS contains five sets of computer programs written in C++ for the calculation of fluid properties. Both model fluids and data from fluid inclusions can be analysed in the programs. Bulk density, molar volume and composition of fluid inclusions are calculated with the program BULK, which uses microthermometric data, micro-Raman spectroscopic data, cation ratios and volume-fraction estimations as input. The program offers a broad variety of equations of state, which are selected according to the fluid system or the temperature and pressure conditions of interest. The isochores that correspond to the output or test V À x properties of fluid inclusions are calculated by the program ISOC. In calculating the isochores, this program takes account of the compressibility and expansion of selected host minerals. The program TEST allows different equations of state to be compared directly with experimental data, thereby facilitating selection of the most adequate model in the programs BULK and ISOC. Loner is a group of programs that handle individual equations of state (EoS) for all fluid systems presented in the programs BULK and ISOC. Aqso is a group of programs that allows purely empirical modelling of electrolyte-bearing aqueous solutions, Henry's law for dilute gas-bearing aqueous solutions, and osmotic coefficients for dilute electrolyte-bearing aqueous solutions.
Keywords: Fluid inclusions; Thermodynamic modelling; Equations of state; Isochores; Computer programs; C++